2021
DOI: 10.2147/ijgm.s330924
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Joint Infection Caused by Mycoplasma hominis, Diagnosed Using Metagenomic Sequencing

Abstract: To our knowledge, the periprosthetic joint infection (PJI) caused by Mycoplasma hominis is a rare postoperative complication after total knee arthroplasty (TKA). Just a few cases associated with Mycoplasma hominis infection after TKA were reported all over the world currently. In view of the difficulty involved in isolating this microorganism, Mycoplasma hominis infection may be under-recognized and should be considered in culture-negative cases where the microbial etiology is not easily identified. Metagenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, septic arthritis caused by M. hominis (Ali et al, 2021a) as well as U. parvum (MacKenzie et al, 2010) has been reported in immunosuppressed patients. M. hominis has been identified as a novel periprosthetic joint infection (a rare postoperative complication) using a new tool called "metagenomic sequencing" (Wang et al, 2021a). M. hominis also might cause brain abscesses (Whitson et al, 2014).…”
Section: Mycoplasma Infection and Urogenital Diseasesmentioning
confidence: 99%
“…In addition, septic arthritis caused by M. hominis (Ali et al, 2021a) as well as U. parvum (MacKenzie et al, 2010) has been reported in immunosuppressed patients. M. hominis has been identified as a novel periprosthetic joint infection (a rare postoperative complication) using a new tool called "metagenomic sequencing" (Wang et al, 2021a). M. hominis also might cause brain abscesses (Whitson et al, 2014).…”
Section: Mycoplasma Infection and Urogenital Diseasesmentioning
confidence: 99%
“…mNGS can detect all pathogenic bacteria in samples without bias, and has significant advantages in detecting some rare bacteria, fastidious bacteria and other rare pathogenic bacteria (Thoendel et al, 2017;He et al, 2020). Wang et al (Wang et al, 2021) reported a case of knee PJI infected by Mycoplasma hominis, in which Wang et al innovatively introduced mNGS to detect pathogenic bacteria (Wang et al, 2021). mNGS results indicated that the pathogenic bacteria might be Mycoplasma hominis for twice.…”
Section: Discussionmentioning
confidence: 99%
“…They all isolated Mycoplasma by routine microbial culture methods. The difference was that Xiang et al (Wang et al, 2021) and Sneller et al (Sneller et al, 1986) isolated Mycoplasma from blood agar, but Muramatsu et al (Muramatsu et al, 2022), on the other hand, isolated pathogenic bacteria the blood bottles. Notably, Mycoplasma can be easily missed because its small well-defined colonies on agar.…”
Section: Discussionmentioning
confidence: 99%
“…What is more worrying is that M . hominis is gram‐negative due to its lack of cell wall and has no response to all antibiotics targeting cell wall synthesis 12 . This special biological characteristic makes it can not only escape the routine etiological examination such as Gram staining, but also escape the clinician's empirical anti‐infection treatment.…”
Section: Discussionmentioning
confidence: 99%
“…What is more worrying is that M. hominis is gram-negative due to its lack of cell wall and has no response to all antibiotics targeting cell wall synthesis. 12 This special biological characteristic makes it can not only escape the routine etiological examination such as Gram staining, but also escape the clinician's empirical anti-infection treatment. The growth rate of Mycoplasma on the blood agar medium routinely used for pathogen proliferation is slower than that of common bacteria, it usually takes 48 h or even longer, and the colony morphology is not typical.…”
Section: Discussionmentioning
confidence: 99%